PERAN GURU PAI DALAM MEMBINA AKHLAKUL KARIMAH SISWA DI ERA DIGITAL DI SMPIT AS-SALAM MALANG - Cholis Dinina Istikhomah; Rosichin Mansur; Muhammad Fahmi Hidayatullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Moral development in Islam is a very important process in life, both in the family environment and in society in general, especially with the current state of the art full of the digital era no longer using human labor, education can also progress very quickly but the risk of many children being children who are addicted to gadgets so that socialization with the environment is greatly reduced because they are busy with gadgets, with the existing reality giving rise to good and bad effects on students. This is the background for conducting descriptive research on what is morals, how is the habituation of PAI teachers in fostering student morals, how are the results of PAI teachers in fostering student morals, and what is the role of PAI teachers in fostering student morals. morals of students at SMPIT As-Salam Miskin. This research was started on June 14-17, 2022. The subjects of this research were teachers, especially PAI teachers, and students. This study uses qualitative research techniques to understand what phenomena are experienced by research subjects. The results of the study include: 1) the moral condition of students, 2) increasing the development of students' morals, 3) getting used to the development of students' morals.